Ein kritisch-multiperspektivischer Blick auf Forschendes Lernen in der Lehrkräftebildung - Bloh, Thiemo; Caruso, Carina (die hochschullehre)
Forschendes Lernen in der Lehrer:innenbildung ist seit der Ausweitung schulpraktischer Anteile bzw. der Einführung des sogenannten Praxissemesters eng verwoben mit der Lehrer:innenausbildung. Gleichzeitig wird bisher weitestgehend different beantwortet, was Forschendes Lernen ist und sein kann sowie warum es wie hochschuldidaktisch gerahmt wird und werden sollte. Der Beitrag widmet sich dieser Frage. Dabei zeigt sich einerseits, dass hochschuldidaktische Zugänge zur Realisierung Forschenden Lernens in der Lehrer:innenbildung erst vor dem Hintergrund theoretischer Annahmen zur Entwicklung von Lehrpersonen und deren Professionalität sowie zur Gestalt - gemeint ist hier der Beitrag zu dieser Entwicklung sowie der Anteil an Professionalität - Forschenden Lernens entwickelt werden können, eine solche Fundierung aber oftmals ausbleibt. Andererseits wird herausgearbeitet, inwiefern eine Differenz zwischen wissenschaftlicher Forschung und Forschung im Forschenden Lernen besteht. Daran anschließend wird eine habitustheoretische Fundierung Forschenden Lernens vorgestellt und es werden exemplarisch deren Implikationen für die Gestaltung Forschenden Lernens benannt. Abschließend wird anhand empirischer Rekonstruktionen beispielhaft eine praktische Umsetzung diskutiert.
Keywords: Forschendes Lernen; Lehrer:innenausbildung; Praxissemester; Professionalisierung / Research-based learning; teacher education; internships; professionalization

Insights into the decomposition of zirconium acetylacetonate using synchrotron radiation: Routes to the formation of volatile Zr-intermediates - Grimm, Sebastian; Baik, Seung-Jin; Hemberger, Patrick; Kasper, Tina; Kempf, Andreas M.; Atakan, Burak (Journal of Materials Research)
Abstract The thermal decomposition of Zr(acac) 4 is studied in a SiC-microreactor on the micro-second time scale. By utilizing synchrotron radiation and photoelectron photoion coincidence spectroscopy, six important zirconium intermediates, as for instance Zr(C 5 H 7 O 2 ) 2 (C 5 H 6 O 2 ), and Zr(C 5 H 6 O 2 ) 2 , are identified in the gas phase for the first time. The adiabatic ionization thresholds of intermediately formed zirconium species are estimated and the main products of their thermal decomposition, acetylacetone, acetylallene and acetone are characterized unambiguously and isomer-selectively. Based on all detected intermediates, we deduce the predominant pyrolysis pathways of the precursor in the temperature range from 400 to 900 K. Our findings are complemented by numerical simulations of the flow field in the microreactor, which show that the choice of dilution gas significantly influences the temperature profile and residence times in the microreactor, such that helium provides a more uniform flow field than argon and should preferentially be used. Graphical abstract Using a soft ionization method coupled to velocity map imaging (VMI), leads to valuable insights in the thermal decomposition of Zr(C 5 H 7 O 2 ) 4 , used in the synthesis of functional nanomaterials and ceramic coatings. Thanks to the use of a microreactor, important gas
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Mechanism and Kinetics of the Thermal Decomposition of Fe(C5H5)2 in Inert and Reductive Atmosphere: A Synchrotron‐Assisted Investigation in A Microreactor - Grimm, Sebastian; Hemberger, Patrick; Kasper, Tina; Atakan, Burak (Advanced Materials Interfaces)
Abstract The decomposition and reduction of ferrocene, an important precursor for iron chemical vapor deposition and catalyst for nanotube synthesis, is investigated in the gas‐phase. Reactive intermediates are detected to understand the underlying chemistry by using a microreactor coupled to a synchrotron light source. Utilizing soft photoionization coupled with photoelectron‐photoion coincidence detection enables us to characterize exclusive intermediates isomer‐selectively. A reaction mechanism for the ferrocene decomposition is proposed, which proceeds as a two‐step process. Initially, the molecule decomposes in a homogeneous surface reaction at temperatures <900 K, leading to products such as cyclopentadiene and cyclopentadienyl radicals that are immediately released to the gas‐phase. At higher temperatures, ferrocene rapidly decomposes in the gas‐phase, losing two cyclopentadienyl radicals in conjunction with iron. The addition of hydrogen to the reaction mixture reduces the decomposition temperature, and changes the branching ratio of the products. This change is mainly attributed to the H‐addition of cyclopentadienyl radicals on the surface, which leads to a release of cyclopentadiene into the gas‐phase. On the surface, ligand fragments may also undergo a series of catalytic H‐losses leading most probably to a high carbon content in the film. Finally, Arrhenius parameters for both global reactions are presented.
Keywords: Mechanical Engineering; Mechanics of Materials

Jupyter Notebooks for Teaching, Learning, and Doing Data Science - Fleischer, Yannik; Hüsing, Sven; Biehler, Rolf; Podworny, Susanne; Schulte, Carsten (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
We report on our work with students in our data science courses, focusing on the analysis of students’ results. This study represents an in-depth analysis of students’ creation and documentation of machine learning models. The students were supported by educationally designed Jupyter Notebooks, which are used as worked examples. Using the worked example, students document their results in a so-called computational essay. We examine which aspects of creating computational essays are difficult for students to find out how worked examples should be designed to support students without being too prescriptive. We analyze the computational essays produced by students and draw consequences for redesigning our worked example.

Model-based design of a segmented reactor for the flexible operation of the methanation of CO2 - Herrmann, Felix; Grünewald, Marcus; Riese, Julia (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Demand Side Management in Biogas Plants - Dynamic Simulation of the Influence of Time-varying Agitation on Biogas Production - Lilli, Lilli; Röder, Lilli; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Energy Proceedings)

"Schwangerschaft ressourcenorientiert erleben" (SRE-Studie) - Das Zürcher Ressourcen Modell (ZRM) als Intervention zur Stressreduktion in der Geburtsvorbereitung. - Schneider, Tamara; Weber, Julia; Bauer, Nicola H.

"ProGRess" - Prokrastination reduzieren und Gesundheit fördern. - Schneider, Tamara; Klingsieck, Katrin B.

"Schwangerschaft ressourcenorientiert erleben" (SRE-Studie) - Stressreduktion in der Schwangerschaft mit dem Zürcher Ressourcen Modell (ZRM). - Schneider, Tamara; Weber, Julia; Bauer, Nicola H.

"ProGRess" - Prokrastination ressourcenstark und gesundheitsfördernd begegnen. - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Ressourcen gegen Prokrastination aktivieren und Gesundheit fördern. - Schneider, Tamara; Klingsieck, Katrin B.

Mixed-Signal Baseband Circuit Design for High Data Rate Wireless Communication in Bulk CMOS and SiGe BiCMOS Technologies - Javed, A. R.

Rahmenwerk zur Gestaltung des Technologietransfers in mittelständisch geprägten Innovationsclustern - Fechtelpeter, Christian

Inklusion und Sprachbildung: „Das habe ich noch nie vorher versucht, also bin ich völlig sicher, dass ich es schaffe“ : Eine interdisziplinäre Perspektive auf den Geschichtsunterricht - Altun, Tülay; Günther, Katrin; Markus, Bernhardt (Fachorientierte Sprachbildung und sprachliche Vielfalt in der Lehrkräftebildung: Hochschuldidaktische Formate an der Universität Duisburg-Essen)

"I don' know why I check this..." - Investigating Expert Users' Strategies to Detect Email Signature Spoofing Attacks - Mayer, Peter; Poddebniak, Damian; Fischer, Konstantin; Brinkmann, Marcus; Somorovsky, Juraj; Sasse, Angela; Schinzel, Sebastian; Volkamer, Melanie (Eighteenth Symposium on Usable Privacy and Security (SOUPS 2022))

TLS-Anvil: Adapting Combinatorial Testing for TLS Libraries - Maehren, Marcel; Nieting, Philipp; Hebrok, Sven Niclas; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (31st USENIX Security Symposium (USENIX Security 22))

Reflektierendes Schreiben im Praxissemester. Eine Untersuchung studentischer Schreibprodukte im Kontext der Forschungswerkstätten „Sprachsensible Schulentwicklung“ im Masterstudiengang Bildungswissenschaften an der Universität Duisburg-Essen - Büttner, Denise; Teichwart, Tatienne (Fachorientierte Sprachbildung und sprachliche Vielfalt in der Lehrkräftebildung. Hochschuldidaktische Formate an der Universität Duisburg-Essen)

„Behinderung“ als Thema von Unterricht. Eine rekonstruktive Fallstudie zur (De-)Konstruktion von Dis*ability - Büttner, Denise; Frank, Magnus; Geier, Thomas (Lehren und Lernen in Differenzverhältnissen)

"Bei dir läuft" - Zur Rekonstruktion neuer Sprache in Diskursen migrationsmarkierten Sprachwandels - Frank, Magnus; Büttner, Denise (MPZD)

Viscoelastic Cahn–Hilliard models for tumor growth - Garcke, Harald; Kovács, Balázs; Trautwein, Dennis (Mathematical Models and Methods in Applied Sciences)
We introduce a new phase field model for tumor growth where viscoelastic effects are taken into account. The model is derived from basic thermodynamical principles and consists of a convected Cahn–Hilliard equation with source terms for the tumor cells and a convected reaction–diffusion equation with boundary supply for the nutrient. Chemotactic terms, which are essential for the invasive behavior of tumors, are taken into account. The model is completed by a viscoelastic system consisting of the Navier–Stokes equation for the hydrodynamic quantities, and a general constitutive equation with stress relaxation for the left Cauchy–Green tensor associated with the elastic part of the total mechanical response of the viscoelastic material. For a specific choice of the elastic energy density and with an additional dissipative term accounting for stress diffusion, we prove existence of global-in-time weak solutions of the viscoelastic model for tumor growth in two space dimensions [Formula: see text] by the passage to the limit in a fully-discrete finite element scheme where a CFL condition, i.e. [Formula: see text], is required. Moreover, in arbitrary dimensions [Formula: see text], we show stability and existence of solutions for the fully-discrete finite element scheme, where positive definiteness of the discrete Cauchy–Green tensor is proved with a regularization technique that was first introduced by Barrett and Boyaval [Existence and approximation of a (regularized) Oldroyd-B model, Math. Models Methods Appl. Sci. 21 (2011) 1783–1837]. After that, we improve the regularity results in arbitrary dimensions [Formula: see text] and in two dimensions [Formula: see text], where a CFL condition is required. Then, in two dimensions [Formula: see text], we pass to the limit in the discretization parameters and show that subsequences of discrete solutions converge to a global-in-time weak solution. Finally, we present numerical results in two dimensions [Formula: see text].
Keywords: Applied Mathematics; Modeling and Simulation